Effect of sawing induced micro-crack orientations on fracture properties of silicon wafers. (March 2016) - Azar, Amin S.; Holme, Børge; Nielsen, Øyvind
Abstract: Fixed abrasive wire sawing has become the method of choice for slicing single crystal silicon ingots. During the wafering process, diamond grains penetrate into the silicon while sliding along the material at the speed of several meters per second. This leaves a significant amount of sub-surface damage with micro-cracks near the wafer surface that are oriented in different directions. The micro-crack distribution depends on the general sawing parameters, and on intricate, local details of the sawing process. Handling of sliced wafers with micro-cracks may provide conditions for unstable growth that leads to brittle fracture. In order to categorize the effect of these micro-cracks on the overall fracture strength of the wafers, a number of cracks with different lengths and orientations were modeled. Four-point-bending of a 150 μm thick wafer was simulated. Stress intensity factor ( K C ) and J -Integral ( J C ) approaches were used to define and sort unstable crack lengths and morphologies. It was found that the cracks oriented at 20° and 60° with reference to 〈1 0 0〉 are the most and least vulnerable flaws respectively, under the identical loading conditions.